Electrophysiological markers of preclinical diagnosis of glaucomatous optic neuropathy - M. O. Kirillova (Российский офтальмологический журнал, 2021)
Purpose: to evaluate the changes in electrophysiological indicators reflecting various aspects of the function of retinal ganglion cells (RGC) and their axons in the early diagnosis of glaucomatous optic neuropathy (GON).Material and methods. Two clinical groups, (1) 35 patients (60 eyes) aged 49 to 70 with suspected glaucoma and (2) 16 patients (30 eyes) aged 43–68 with initial primary open-angle glaucoma (POAG), and a comparison group of 38 relatively healthy subjects (45 eyes) aged 42–70 were tested for pattern-reversed visual evoked potentials (PVEP), transient and stationary pattern-ERGs (PERG) according to ISCEV, and photopic negative response (PhNR).Results. The P100 amplitudes in both clinical groups differed significantly from the norm in PVEP on small and large patterns. The elongation of peak latency (T) of P100 compared with norm was significant for the stimulus 1° in group 2. In both groups of patients, increased variability of the temporal parameters of PERG and PVEP for small patterns was found. In groups 1 and 2, a decrease in the amplitude of P50 and N95 peaks of transient PERG for all stimuli was revealed, which was the most significant for the 0.3° pattern. In group 1, the N95 peak was significantly delayed in PERG for large patterns. A statistically significant reduction in the steady-state PERG's amplitude was found in the groups of suspected glaucoma and initial POAG. The sharpest changes were found for small (0.8° and 0.3°) patterns. The elongation of T compared to the norm was most pronounced for PERG at 0.3°, but due to the high variability of temporary indicators within the group, it had no statistical significance. The amplitude of PhNR was significantly different from the norm in the ERG for a flash of 3.0 cd·sec/m2.Conclusion. In patients with suspected glaucoma, a decrease in the P100 VEP amplitude with the simultaneous elongation of T may be considered as a criteria for the plastic stage at the level of lateral geniculate nucleus. Markers of functional changes in RGCs are the decrease in the amplitude of PhNR in response to bright flash, and P50 and N95 of PERG for pattern size 0.3°. The results indicate a greater vulnerability of the parvocellular system to early events in the development of GON.